PENGUATAN NASIONALISME MELALUI AKTIVITAS EKONOMI DI PULAU TERLUAR INDONESIA (STUDI DI PULAU RUPAT KABUPATEN BENGKALIS-RIAU) - Muslim, Muslim; Muklis, Muklis; Romus, Mahendra; Malau, Riki Handri; Rachmadi, M. (Universitas Lancang Kuning, 2023)
The erosion of the sense of nationalism which lies in the threat of disintegration and migration of the population, the people of the border areas must be handled seriously. The development of border areas, especially in the Rupat Island area, has recently undergone many changes. The government with a policy of developing Indonesia from the periphery (border area) as an effort to change the face of the border and the outermost island areas both from the side of the border (border) as well as the accessibility of the community in various services, as well as infrastructure development in the border area has an impact on the economy. This research method uses the Mixed Methods technique which will combine qualitative methods with quantitative methods simultaneously in order to obtain more comprehensive, valid and objective data. The results of the study explain that the construction of road infrastructure and the operation of the